NATIONAL NUTRITION AGENCY’S RESPONSE TO THE FREE NUTRITIOUS MEAL PROGRAM POISONING (CONTENT ANALYSIS ON BGN.GO.ID) - Dwi Pratiwi; Andre Novie Rahmanto; Eka Nada Shofa Alkhajar (Lektur: Jurnal Ilmu Komunikasi, 2026)
This study aims to reveal how the National Nutrition Agency (BGN) communicated its crisis management measures, built a public responsibility image, and maintained institutional accountability amid social pressure following the Free Nutritious Meal Program (MBG) poisoning incident. The research employs a quantitative approach using content analysis based on W. Timothy Coombs’ Situational Crisis Communication Theory (SCCT). The data were collected from 35 news reports, articles, and press releases published on the official website bgn.go.id containing BGN’s statements throughout September 2025. The findings show that the most dominant crisis communication strategy used by BGN was justification (34.29%), followed by excuse (22.86%), reminder (17.14%), apology (11.43%), compensation (5.71%), ingratiation (5.71%), and deny (2.86%), while attack the accuser, scapegoat, and victimage were not found. These results illustrate that BGN primarily applied the diminish and rebuild strategies, complemented by bolstering and deny as secondary approaches to strengthen the institution’s image and credibility.